Correction: Super-large dendrites composed of trigonal PbO2 nanoplates with enhanced performances for electrochemical devices. Issue 94 (13th November 2020) - Ding, Liang-Xin; Zheng, Fu-Lin; Wang, Jian-Wei; Li, Gao-Ren; Wang, Zi-Long; Tong, Ye-Xiang
Abstract : Correction for 'Super-large dendrites composed of trigonal PbO2 nanoplates with enhanced performances for electrochemical devices' by Liang-Xin Ding et al., Chem. Commun., 2012, 1275–1277, DOI: ; 10.1039/C2CC15271A .